2018
DOI: 10.18203/2320-1770.ijrcog20180057
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of diagnostic hysteroscopy in abnormal uterine bleeding and its histopathological correlation

Abstract: Background: Abnormal uterine bleeding is a common clinical problem with myriad of causes. The diagnosis and management of abnormal menstrual function must be based on an understanding of the physiologic mechanisms involved in the regulation of the normal cycles. Diagnostic hysteroscopy is a valuable tool in diagnosing structural intra-cavital pathology, very suitable for out-patient clinic.Methods: This is a prospective study which has been carried out in the Department of Obstetrics and Gynecology, Tirunelvel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…European society of human reproduction and embryology conducted a study on hysteroscopy with endometrial biopsy and thus concluded that the hysteroscopy with endometrial biopsy is the "Gold standard" to investigate abnormal uterine bleeding [19][20][21][22] . Dilatation and curettage was considered as obsolete because it is a blind procedure with a complication rate of 6% to 8% and low sensitivity for local and pedunculated intracavitary lesions [9,16] . The Lesions were more accurately visualized through hysteroscopy therefore biopsy can be done simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…European society of human reproduction and embryology conducted a study on hysteroscopy with endometrial biopsy and thus concluded that the hysteroscopy with endometrial biopsy is the "Gold standard" to investigate abnormal uterine bleeding [19][20][21][22] . Dilatation and curettage was considered as obsolete because it is a blind procedure with a complication rate of 6% to 8% and low sensitivity for local and pedunculated intracavitary lesions [9,16] . The Lesions were more accurately visualized through hysteroscopy therefore biopsy can be done simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Multiparous, nulliparous and grand multiparous 3. Patients did not require emergency treatment [16] Exclusion criteria 1. Patients with profuse bleeding and large fibroids or multiple fibroids.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations